2016
DOI: 10.1111/cen.13143
|View full text |Cite
|
Sign up to set email alerts
|

Using a thyroid disease-free population to define the reference interval for TSH and free T4 on the Abbott Architect analyser

Abstract: A substantial proportion of apparently healthy persons have subclinical thyroid disease. These subjects must be excluded for any thyroid hormone reference interval studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…4 Recently, Hickman and colleagues reported no age or sex-related differences in TSH and FT4 levels. 15…”
Section: Discussionmentioning
confidence: 99%
“…4 Recently, Hickman and colleagues reported no age or sex-related differences in TSH and FT4 levels. 15…”
Section: Discussionmentioning
confidence: 99%
“…These comparisons were performed by comparing the lower and upper reference interval limits of this study's reference intervals with those of other studies previously reported in medical literature. Results indicate that for TSH, this study's gender independent lower reference interval limit is lower than that of Darfur (Sudan) (Ali et al, 2018), British (Kratzsch et al, 2005) [12] , Australian (Hickman et al, 2017) [8] , American (Hollowell et al,20) [9] , and Srpska Republic (Mirjani-Azaric et al, 2017) [15] populations, and gender dependent upper reference interval limit for Khartoum (Sudan) (Musa et al, 2018) [16] population. However, the gender independent upper reference interval limit for TSH in this study is higher than that of gender independent upper reference interval limits for Darfur (Sudan) (Ali et al, 2018), British (Kratzsch et al, 2005) [12] , Australian (Hickman et al, 2017) [8] , American (Hollowell et al, 20) [9] , and Srpska Republic (Mirjani-Azaric et al, 2017) [15] populations, and gender dependent upper reference interval limit for Khartoum (Sudan) (Musa et al, 2018) [16] population.…”
Section: Comparison Of Developed Reference Intervals For Thyroid Horm...mentioning
confidence: 57%
“…Results indicate that for TSH, this study's gender independent lower reference interval limit is lower than that of Darfur (Sudan) (Ali et al, 2018), British (Kratzsch et al, 2005) [12] , Australian (Hickman et al, 2017) [8] , American (Hollowell et al,20) [9] , and Srpska Republic (Mirjani-Azaric et al, 2017) [15] populations, and gender dependent upper reference interval limit for Khartoum (Sudan) (Musa et al, 2018) [16] population. However, the gender independent upper reference interval limit for TSH in this study is higher than that of gender independent upper reference interval limits for Darfur (Sudan) (Ali et al, 2018), British (Kratzsch et al, 2005) [12] , Australian (Hickman et al, 2017) [8] , American (Hollowell et al, 20) [9] , and Srpska Republic (Mirjani-Azaric et al, 2017) [15] populations, and gender dependent upper reference interval limit for Khartoum (Sudan) (Musa et al, 2018) [16] population. For T3, this study's gender independent lower reference interval limit is lower than that of gender dependent British (Kratzsch et al, 2005) [12] population, and similar to that of Srpska Republic (Mirjani-Azaric et al, 2017) [15] population, while the upper reference interval limit is higher than that of British (Kratzsch et al, 2005) [12] population, and lower than that of the Srpska Republic (Mirjani-Azaric et al, 2017) [15] population.…”
Section: Comparison Of Developed Reference Intervals For Thyroid Horm...mentioning
confidence: 57%
See 1 more Smart Citation
“…For the Abbott Architect we identified 12 TSH RI studies in the literature (see Table 1) but only 6 are NACB compliant with direct TSH testing and TPO-Ab screening. Even on the same analytical platform the LRL for the Abbott Architect TSH can vary from 0.17-0.54 mU/L while the URL ranged from 2.82-6.2 mU/L [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%